The Coloniality of Migration and the “Refugee Crisis”: On the Asylum-Migration Nexus, the Transatlantic White European Settler Colonialism-Migration and Racial Capitalism - Gutiérrez Rodríguez, Encarnación (Refuge: Canada's Journal on Refugees, 2018)
This article departs from the discussion by Stephen Castles on the migration-asylum nexus by focusing on the political and cultural effects of the summer of immigration in 2015. It argues for a conceptualization of the asylum-migration nexus within the framework of Anibal Quijano’s “coloniality of power” by developing the analytical framework of the “coloniality of migration.” Through the analytical framework of the “coloniality of migration” the connection between racial capitalism and the asylum-migration nexus is explored. It does so by first focusing on the economic and political links between asylum and migration, and how both constitute each other. On these grounds, it discusses how asylum and migration policies produce hierarchical categories of migrants and refugees, producing a nomenclature drawing on an imaginary reminiscent of the orientalist and racialized practices of European colonialism and imperialism. In a second step, it focuses on migration and asylum policies as inherent to a logic of racialization of the workforce. It does so by first exploring the racial coding of immigration policies within the context of settler colonialism and transatlantic White European migration to the Américas and Oceania in the nineteenth and twentieth centuries, and second, by discussing migration policies in post-1945 Western Europe.